Hydrogen storage performance of the as-milled YMgNi alloy catalyzed by CeO2. (18th January 2018) - Zhang, Yanghuan; Li, Yaqin; Shang, Hongwei; Yuan, Zeming; Qi, Yan; Dong, Xiaoping; Guo, Shihai
Abstract: The YMgNi-based YMg11 Ni + 5 wt%CeO2 (named YMg11 Ni5CeO2 ) alloys were prepared by using mechanical ball milling. The influences of CeO2 on the structure and gaseous hydrogen storage performance of YMg11 Ni alloy were studied systematically. The structures of sample alloy were determined by X-ray diffraction (XRD) and high resolution transmission electron microscope (HRTEM). The gaseous hydrogen storage performances were tested by using an automatically controlled Sieverts apparatus. The dehydrogenation performance was studied by thermogravimetry (TG) and differential scanning calorimetry (DSC). The hydrogen desorption activation energy was calculated by adopting Kissinger methods. The results show that adding CeO2 into YMg11 Ni can lower the hydrogen storage thermodynamics slightly and increase the hydrogen absorption/desorption rate obviously. Moreover, the hydrogen desorption activation energy ( E de (k)) of the alloys is 91.53 kJ mol −1 for YMg11 Ni alloy and 74.89 kJ mol −1 for YMg11 Ni5CeO2 alloy, respectively. This is because the hydrogen desorption kinetic of the alloy is improved by adding catalyst CeO2 . Highlights: The YMg11 Ni +5 wt% CeO2 alloy was prepared by mechanical milling. Effect of CeO2 on the hydrogen storage properties of the alloy was studied. Adding CeO2 can effectively lower the decomposition temperature of hydrides. The kinetics performance of the alloy can be improved by adding CeO2 . The addition of CeO2 obviously reduces the dehydrogenation activation energy.